Northern sustainabilities : understanding and addressing change in the circumpolar world - Fondahl, Gail; Wilson, Gary N. 1967- (Springer Polar sciences., 2017)
This edited volume examines the multiple dimensions of sustainability in the Circumpolar North, a territory facing unprecedented environmental and social challenges at the start of the 21st century. The chapters explore the cultural, economic, political and environmental aspects of sustainability, as well as examples of successful research collaboration with northern and indigenous communities. By examining a wide range of issues and places, the contributions highlight the diversity of the Circumpolar North, the challenges and opportunities it faces, and the ways in which people and communities are adapting to and influencing the changing circumstances of this dynamic region. Contributors include both Indigenous and non-Indigenous researchers from eleven different countries and from across the career spectrum. This book will appeal to an academic audience interested in the manifold facets of sustainability in the Arctic and sub-arctic regions of the world.